New species of Preussia with 8-celled ascospores (Sporormiaceae, Pleosporales, Ascomycota) - Kruys, Åsa (Phytotaxa, 2015)
The focus of this study is on Preussia sensu lato species with 8-celled ascospores. Two new species, P. alpina and P. octocylindrospora are introduced based on morphological characters and discussed in relation to similar species in the genus. New records are provided from Sporormiella corynespora, S. octomegaspora, P. octomera and P. octonalis. This greatly expands or reduces their geographical distribution ranges, as well as substrate preferences. In addition, a key to the coprophilous species with 8-celled ascospores is provided.